Windows into a revolution
1 online resource (xii, 337 pages)
Keywords: "Windows into a Revolution edited by Alpa Shah and Judith Pettigrew, the first book in the series offers glimpses into the spread of Maoism in India and Nepal by tracing some of its effects on the lives of ordinary people living amidst the revolutions. Weaving through the nostalgic reflections of former Bengali Naxalites; the resurgence of ancestral conflicts in the spread of the Maoists in the remote hills of western Nepal; the disillusionments of dalits of central Bihar in the policies of the cadres; to the complexities of the interrelationship between non-aligned civilians and insurgents in central Nepal, the book offers a series of windows into different stages of mobilization and transformation into what are, were or may become, revolutionary strongholds."--Provided by publisher.